CircCDK14 ameliorates interleukin-1β-induced chondrocyte damage by the miR-1183/KLF5 pathway in osteoarthritis - Lai, Xiaowei; Song, Yali; Tian, Jimei (Autoimmunity (Chur, Switzerland), 2022)
The pathogenesis of osteoarthritis (OA), an endemic and debilitating disease, remains unclear. The study aimed to reveal the role of circular RNA cyclin dependent kinase 14 (circCDK14) in OA development and the underlying mechanism. Human chondrocytes were stimulated by 10 ng/mL interleukin-1β (IL-1β) to mimic OA cell model. The RNA expression of circCDK14, microRNA-1183 (miR-1183) and kruppel like factor 5 (KLF5) was checked through quantitative real-time polymerase chain reaction. Western blot was employed to detect protein expression. Cell viability, proliferation and apoptosis were investigated by cell counting kit-8, 5-Ethynyl-29-deoxyuridine and flow cytometry analysis, respectively. Starbase online database was performed to identify the interaction between miR-1183 and circCDK14 or KLF5. Exosomes were isolated by differential centrifugation and identified by transmission electron microscopy, nanoparticle tracking analysis and western blot analysis. CircCDK14 and KLF5 expression were significantly decreased, while miR-1183 was increased in OA cartilage tissues and IL-1β-treated chondrocytes in comparison with controls. CircCDK14 overexpression attenuated the inhibitory effect of IL-1β treatment on cell proliferation and the promoting effects on cell apoptosis and extracellular matrix degradation. Additionally, miR-1183 was targeted by circCDK14, and miR-1183 mimics reversed circCDK14-mediated actions in IL-1β-treated chondrocytes. The knockdown of KLF5, a target mRNA of miR-1183, also rescued the effects of miR-1183 inhibitors in IL-1β-induced chondrocytes. Moreover, circCDK14 could induce KLF5 expression by interacting with miR-1183. Further, exosomal circCDK14 had a high diagnostic value in OA. CircCDK14 reintroduction assuaged IL-1β-caused chondrocyte damage by the miR-1183/KLF5 pathway, providing a diagnostic biomarker for OA.